Crisis in Ukraine 2014-2016 Reporting in the British Press - Anton B. Geht; Daria A. Patrusheva; Bogdan K. Reznikov; Denis V. Shutman (Научный диалог, 2020)
This work is devoted to studying the issue of how the events of the political crisis of 2014-2016 in Ukraine were reflected in the UK media. The main features of the British print media are highlighted, the characteristic features of the British newspaper and journalistic discourse are revealed. The study was conducted on the basis of journalistic texts of 2014-2016. The appearance and transformation of the prevailing in the UK opinions about the Ukrainian crisis and its assessments in the press are shown. It raises the issue of coverage by the British media of a referendum on the entry of Crimea into the Russian Federation, the armed confrontation in the South-East of Ukraine and the conclusion of the Minsk agreements. The authors infer that over the course of two years there has been a noticeable change in the tone and rhetoric of newspaper publications in British press: if in 2014 the judgments of the journalists were mostly pronounced negative, then over time the estimates became more balanced and restrained. It is noted that by the end of 2015 there was a noticeable decline in interest from large British print media to cover the Ukrainian conflict, which was manifested in a noticeable reduction in publications affecting this topic.